If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 9) + x = 2(x + 5) + -2 Reorder the terms: 9(9 + x) + x = 2(x + 5) + -2 (9 * 9 + x * 9) + x = 2(x + 5) + -2 (81 + 9x) + x = 2(x + 5) + -2 Combine like terms: 9x + x = 10x 81 + 10x = 2(x + 5) + -2 Reorder the terms: 81 + 10x = 2(5 + x) + -2 81 + 10x = (5 * 2 + x * 2) + -2 81 + 10x = (10 + 2x) + -2 Reorder the terms: 81 + 10x = 10 + -2 + 2x Combine like terms: 10 + -2 = 8 81 + 10x = 8 + 2x Solving 81 + 10x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 81 + 10x + -2x = 8 + 2x + -2x Combine like terms: 10x + -2x = 8x 81 + 8x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 81 + 8x = 8 + 0 81 + 8x = 8 Add '-81' to each side of the equation. 81 + -81 + 8x = 8 + -81 Combine like terms: 81 + -81 = 0 0 + 8x = 8 + -81 8x = 8 + -81 Combine like terms: 8 + -81 = -73 8x = -73 Divide each side by '8'. x = -9.125 Simplifying x = -9.125
| 4(x+10)+x=3(x+2) | | -7x-6=8 | | 22+3x=5x | | 7+3x=17-x | | 0.1x-2.6=0.4(x-5) | | 7-3x=17+x | | 4y+12(2y+10)=92 | | 10x+30-9x+27=8x+24 | | 48+2x=8x | | 8y^2+10y+3=0 | | 10x+30-9x-27=8x+24 | | 6x+23=14x-73 | | 10(x+3)-9(x-3)=8(x+3) | | 4x+4.6=9.2 | | 6x+23=17x-73 | | 3b^2-7b+2=0 | | 14-(x+5)=5x-3 | | 215=8 | | 2(5x-6)=4(3+x) | | -3(x+3)+4=5(x+2)+7 | | 7x-2=2(1+3x) | | 4(3x-1)=6+7x | | 4w^2+17w+15=0 | | 7(n-8)+24=-3n+18 | | 4(2x+3)=26+x | | 8x+9=3(5+2x) | | 4u^2+4u+1=75 | | 3(8+3x)=4(7+2x) | | 2(4x+7)=3(8+x) | | 9x+4=2x+60 | | 5x-7=2(1+x) | | 3(x+5)=21+4x |